Redox-sensitive nanoparticles based on 4-aminothiophenol-carboxymethyl inulin conjugate for budesonide delivery in inflammatory bowel diseases. (1st June 2018) - Sun, Qijuan; Luan, Lin; Arif, Muhammad; Li, Jiaxin; Dong, Quan-Jiang; Gao, Yuanyuan; Chi, Zhe; Liu, Chen-Guang
Graphical abstract: Highlights: We synthesized functional nanoparticles based on the amphiphilic inulin. The nanoparticles have a negative charge and pH/redox sensitivity. The nanoparticles were used as drug delivery loading BDS. It showed excellent therapeutic efficacy in colitis mice model. Abstract: The purpose of this study was to develop an oral nanocarrier as budesonide delivery system and to evaluate its therapeutic potential for inflammatory bowel disease (IBD). The nanoparticles (NPs) based on an amphiphilic inulin polymer with 4-aminothiophenol (ATP) grafted onto carboxymethyl inulin (CMI) were prepared. The particle sizes were about 210.18 nm and had the obvious pH/redox sensitive swelling transitions. The drug-release study of NPs <-- >in vitro showed a low release rate (about 45 wt%) in GSH-free media, whereas high release rate (about 80 wt%) in the media containing 20 mM GSH, exhibiting a redox-responsive property. Further in vivo experiments found the NPs tended to accumulate in inflamed sites, and exerted excellent therapeutic efficacy in comparison to drug suspension in colitis mice model. All the results demonstrated that the redox-sensitive NPs, based on amphiphilic inulin, may be used as colon-targeted drug delivery for the treatment of IBD.